Structural demonstration of an active back-flow flap under wind tunnel conditions - Opitz, S.; Gardner, A.D.; Merz, C.B.; Wolf, C.C. (My University, 2015)
The paper presents a detailed concept for influencing dynamic stall with a surface integrated active back-flow flap on the upper side of an airfoil. The development of the flap from a basic concept to the final wind tunnel experiment is described. Special attention is paid on the selection of flap size and position, the structural concept, the actuation mechanism and the instrumentation. Further, the manufacturing procedure developed to produce a retrofit solution for an existing wind tunnel model is illustrated. The paper closes with first functional tests of actuation mechanism and instrumentation in the wind tunnel. Finally the results from wind tunnel experiments are used to validate the predicted reduction of the pitching moment peak.
Keywords: Test & Evaluation